Toward a (co)relational border? Order, care, and chaos at Nordic borders. (October 2021) - Dowle, Lewis J.
Abstract: The events of the European migration 'crisis' of 2015–2016 left an indelible mark on the continent, evident within each of the four Nordic countries of Denmark, Finland, Norway, and Sweden. Migrant-centered agents (MCAs) played an important role in engaging and managing the border in the form of governmental and non-governmental agents during this time. Discourses of urgency and crisis were used to justify policies and practices to 'mitigate' the situation, administered (and engaged with) by MCAs. What ensued was a complex hybridity of Order, Care, and Chaos in each of the four countries, alongside the expansion and reclaiming of power by the nation-state. This paper uses semi-structured interviews to critically analyze such political unfoldings, drawing on notions of exceptionality, responsibility, and neoliberalization. The term '(Co)Relationality' is proposed to the academy to reflect the reciprocal and re-enforcing relations between states and individuals in the subsequent governing and negotiating of the border, exemplified in the Nordic context. Chrono-political and spatial (co)relationality are put forward and developed regarding the theoretical premise that borders must be studied in relationship.